Finance and Development, December 1981. (Finance and Development; Finance and Development, 1981)
This paper highlights that the financial activity of the IMF reached a new peak in the first three quarters of 1981 in terms of the number of arrangements with members involving high conditionality on the use of the IMF's resources, the total amount of resources committed under existing arrangements, and the magnitude of actual purchases. There were 25 stand-by arrangements in effect at the end of September 1981, as well as 16 extended arrangements. The total amount of resources made available to member countries in the first nine months of 1981 was SDR 9.3 billion.